Pengaruh Tunneling Incentive terhadap Leverage Ratio dan Hedging pada Perusahaan Manufaktur yang Terdaftar di Bei Tahun 2016-2021 - Fitria Dwi Wahyuningsih; Arya Suryani; Ali Akbar (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to: 1) identify, describe and analyze the effect of tunneling incentives on leverage ratio, 2) identify, describe and analyze the effect of tunneling incentives on hedging, 3) identify, describe and analyze the effect of leverage ratio on hedging, and 4) determine, describe and analyze the effect of tunneling incentives on the leverage ratio and hedging in manufacturing companies listed on the IDX for the 2016-2021 period. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange totaling 172 companies. The researcher chose a purposive sampling technique by setting certain considerations or criteria that must be met by the samples used in this study, the samples in this study totaled 27 manufacturing companies that met the predetermined sample criteria. To answer the research objectives, the researcher uses a quantitative research method with a descriptive approach and path analysis (Path Analysis) using the help of SmartPLS (outer model and inner model). The results of the study show that: 1) there is no significant effect between tunneling incentives on the leverage ratio; 2) there is a significant effect between tunneling incentives on hedging; 3) there is a positive and significant leverage ratio on hedging; and 4) simultaneously tunneling incentive (X) has no effect on the variable leverage ratio (Y1) and hedging (Y2).